Borazarenes and borazoles. Flourescence spectrometry and quantum efficiencies in relation to slow neutron counting - Rojo, Enrique Aldo; Videla, G. J.; Molinari, Marcelo Antonio; Lires, Osvaldo Andrés; Casas, L. H. (Northern Ireland, 1964)
Fil: Rojo, Enrique Aldo Comisión Nacional de Energía Atómica; Argentina